Towards a concept of inefficiency in performance and dialogue practice. Issue 3 (3rd July 2019) - Taylor, Linda
ABSTRACT: In this article, I offer a model of practice called Operations of Dialogue. Operations of Dialogue (OoD) is a performative structure for a public event. Enacted dialogues relating to an ethical or political theme or issue form part of a public performance that concludes in an open debate. I argue that OoD positions its participants in a critical relation to neoliberal subjectivity, with the potential to usefully inform our modes of teaching and learning. In doing so, I draw upon Jürgen Habermas' theory of communicative action to offer an account of inefficiency in performance and dialogic practice.